A review of cardiac manifestations and predictors of outcome in patients with COVID – 19 - Mishra, Ajay Kumar (Heart Lung, 2020)
Coronavirus disease (COVID-19) pandemic has so far involved 184 countries and more than 2.79 million patients worldwide. Over the past three months, it has attributed to more than 196,000 deaths, with more than 50,000 deaths in the United States alone. Pulmonary manifestations are predominant and have been well identified. Cardiac involvement is also common. Acute cardiac injury, the most common cardiac manifestation of this disease can be seen in patients even without prior cardiac comorbidities. Established cardiovascular risk factors such as diabetes mellitus, hypertension, and coronary artery disease predispose to cardiac injury, the severity of illness and mortality. Non-ischemic myocardial injury secondary to cytokine storm is thought to be the predominant mechanism of acute cardiac injury associated with COVID-19. Multiple mechanisms and processes contribute to cardiac injury resulting in a poor outcome. Some of these are not clearly understood. Clinical and diagnostic details of cardiovascular involvement in these patients are mostly limited to biochemical markers. Multiple therapeutic agents have been tried with questionable efficacy and without clinical evidence. Interactions of comorbidities, cardiovascular drugs, the cardiac effect of therapeutic agents on the illness continue to be under investigation. With an increasing number of patients, newer promising therapies, and ongoing clinical trials, the exact mechanisms and extent to which these risk factors contribute to outcomes will be clearer in the future.